We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
32
1
avatar+649 

 If r = −6, s = −2, and t = −3 then

 

−t(r − s) =

 

A) −24

B) −12

C) 12

D) 20

E) 24

 Sep 12, 2019

Best Answer 

 #1
avatar+18868 
+3

Substitute in the values given for the letters and you have:

 

- (-3)(-6-(-2))=

3 (-6+2) =

3 (-4) = - 12

 
 Sep 12, 2019
 #1
avatar+18868 
+3
Best Answer

Substitute in the values given for the letters and you have:

 

- (-3)(-6-(-2))=

3 (-6+2) =

3 (-4) = - 12

 
ElectricPavlov Sep 12, 2019

33 Online Users

avatar
avatar
avatar
avatar